DIGITAL FORENSICS IN PHOTOGRAPHY EDUCATION - Samrat, Bhavuk; Kaushik, Bhawna; Gupta, Peeyush Kumar; Prabu, S Igni Sabasti; Suri, Sahil; Patil, Pradnya Yuvraj (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The digital photographic history has transformed the principle of authenticity and novel educational patterns are to be established based on balanced models of creativity and forensic consciousness. As image manipulation grows and the images created by AI become more sophisticated, however, the education of photography should be not only artistically sophisticated but also analytical and morally capable. Including the digital forensics course in the curriculum, the learners will be given an opportunity to acquire the understanding of the perception of pictures as aesthetic and evidential objects and relate visual semiotics to the mechanism of data verification. Through the approaches of metadata inspection, analysis of error levels, and artificial intelligence check-up of authenticity, the students end up having a moderate opinion regarding the compatibility of creative expression and digital integrity. Based on the experimental outcomes, the precision, perceptive observation and ethical judgment are increased significantly once the technologies in the field of forensics are incorporated into innovative learning environments. This combination of art, science, and ethics in this model creates a species of photographers that is highly accurate in their technicality, highly philosophical in their thinking capabilities and ethically accountable. This paper intends to capture the essence of digital forensics as an essential part of learning by introducing authenticity as an interactive process of creativity and validation as one of the fundamental aspects of becoming a responsible and well-educated visual practitioner.